A chicken and maize situation: The poultry feed sector in Ghana - Andam, Kwaw S.; Johnson, Michael E.; Ragasa, Catherine; Kufoalor, Doreen S.; Gupta, Sunipa Das (International Food Policy Research Institute, 2017)
This study focuses on the feed milling industry, which serves as the link between maize and poultry, through a field assessment of feed millers in Ghana. The findings establish the importance of feed in the poultry value chain. In addition, they show how the sector has become more integrated with poultry production, especially on larger-scale poultry farms. Because maize accounts for 60 percent of poultry feed, its availability and price have important implications for the profitability and growth potential of feed and, therefore, for poultry production as well. We illustrate these linkages by means of a simple spatial market equilibrium model that ties together the three sectors of the poultry value chain: the primary inputs (maize and soybeans), intermediate inputs (feed), and final products (meat and eggs). This model also enables us to assess the future growth potential of the poultry industry given alternative policy-driven changes in productivity and the production capacities of all three sectors. The results show that for poultry meat, replacing imports with domestic production in the short term would be nearly impossible. For the egg industry, however, there is potential for Ghana to export to neighboring countries by reducing production costs through improvements in yellow maize production.